MORPHOLOGICAL STUDY OF Cerambyx cerdo LINNAEUS, 1758 (COLEOPTERA : CERAMBYCIDAE) FROM DUHOK PROVINCE, KURDISTAN REGION-IRAQ. - BAPIR , TAHSEEN TAHA; ISMAEL, HALGURD RASHED (Journal of Duhok University, 2022)
The present study is a morphological description of Cerambyx cerdo L. 1758 which was collected from different localities of Duhok province, Kurdistan region-Iraq. The species is morphologically has been described and illustrated in detail. The most important diagnostic and taxonomic characters were studied. The locality, general distribution, collecting date and host plant of this species has been recorded